Grain sorghum grown as second crop and inoculated with Azospirillum brasilense associated with nitrogen fertilization - de Asevedo Soares, Deyvison [UNESP]; Andreotti, Marcelo [UNESP]; Vicentini, Maria Elisa [UNESP]; Freitas, Leandro Alves; Modesto, Viviane Cristina [UNESP]; Nakao, Allan Hisashi; Dickmann, Lourdes [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP] (Revista de Agricultura Neotropical, 2021)
Nitrogen fertilization in off-season sorghum may have lower cost-benefit ratios than expected due to the residual effect of previous crops. However, the use of growth-promoting bacteria can be an economical alternative to increase crop yields in Cerrado. The objective was to evaluate the response of grain sorghumto nitrogen fertilization and its inoculation by Azospirillum brasilense. This study aims to evaluate grain sorghumresponses to nitrogen fertilization and A. brasilense inoculation. The experiment was carried out in a fully randomized block design and 5 x 2 factorial scheme, with five replications. Treatments consisted of applying N recommendation (120 kg N-urea ha-1) split as follows:100% at sowing, 100% as topdressing, 25% at sowing and 75% as topdressing, 50% at sowing and 50% as topdressing, and a control (without application), all these with and without A. brasilense seed inoculation. We also assessed the morphological and productivity components of grain sorghum. The application of 100% N at sowing promoted taller plants, while 50% -50% splitting shorter ones. Overall, grain sorghum plants did not respond to A.brasilense inoculation. Moreover, yield components of rainfed sorghumgrown in succession to soybeans were not affected by A. brasilense inoculation and N supplied at once or split.
Sorgo granífero em segunda safra inoculado com Azospirillum brasilense associado a adubação nitrogenada
Keywords: Crop succession; PGPB; Sorghum bicolor; Splitting